2018
DOI: 10.1111/scs.12587
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among people with psychiatric disabilities attending community‐based day centres or Clubhouses

Abstract: Both approaches were suited for supporting their users in maintaining QOL. Visiting clubhouses seems, however, advantageous for QOL in a longer-term perspective. Although this study contributed some new knowledge, research should further address which circumstances are associated with maintaining stability in QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The environment of implementing recovery services were community-based interventions, residential facility setting and services via psychiatric day hospital/primary health care settings (25-30) ( Table 3). Four papers suggested that recovery services can be offered through home-based cares (31-34) and a day centre structure programme (35)(36)(37).…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…The environment of implementing recovery services were community-based interventions, residential facility setting and services via psychiatric day hospital/primary health care settings (25-30) ( Table 3). Four papers suggested that recovery services can be offered through home-based cares (31-34) and a day centre structure programme (35)(36)(37).…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Two studies examined relationships between social network metrics and quality of life (QoL). Hultqvist et al (2018) found that attendance at a Clubhouse program was the strongest predictor of QoL for Clubhouse members but did not find a significant association between social network size and QoL. However, Biegel, Pernice-Duca, Chang, & D’Angelo (2013) found an association between higher quality of social life and whether a participant reported a peer network.…”
Section: Resultsmentioning
confidence: 91%
“…DC attendees reported smaller and less stable social networks compared to Clubhouse members, and DC attendees were more likely to report “professionals” or “no one at all” when asked to identify “someone with whom you can share your innermost thoughts and feelings” compared to Clubhouse members who were more likely to report friends (Hultqvist et al, 2016). DC and Clubhouse participants reported comparable quality of life scores across several domains, including moderate levels of satisfaction with social relationships (Hultqvist et al, 2018). Both authors noted potential selection biases (e.g., psychosocial functioning) that may impact comparisons between Clubhouse and other programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The environment of implementing recovery services were the community, residential facility and services via psychiatric hospital and primary health care settings (26)(27)(28)(29)(30)(31) (Table 3). Four papers suggested that recovery services can be offered through home-based cares (32)(33)(34)(35) and a day centre structure programme (36)(37)(38).…”
Section: Environment For Implementing Recovery Servicesmentioning
confidence: 99%